Law Student's Legal Attitude Towards Campus' Smoking Ban Policy - Laura Cecilia; Maureen Cornellia David (Rechtsidee, 2020)
Cigarettes is a major national issue, especially amongst University students. An estimated 3.3 million votary will die of lung related diseases. This study discusses the law against students in the University Environment. The analysis was carried out using descriptive conceptual dams from KTR policies applied from each tertiary institution. The participating factors were the commitment of the local government, binding law enforcement, written restrictions on a place, positive support from the education sector and the active role of campus organizations. In addition, this journal was submitted to discuss students' opinions about the smoking ban in the campus environment and the number of cigarettes spent on each expenditure as well as the psychological effects obtained after smoking.